PENGGUNAAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN HASIL BELAJAR SISWA TENTANG KEBERAGAMAN SUKU BANGSA SISWA KELAS V UPTD SD NEGERI 33 PAREPARE - Ritha Tuken; Yonathan S Pasinggi (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2022)
This research is motivated by the learning outcomes of students who have not yet reached the SKBM in Class V UPTD SD Negeri 33 Parepare. The purpose of this research was to find out the process of using audio-visual media for fifth grade UPTD SD Negeri 33 Parepare students. The subjects in this study were all students of class V UPTD SD Negeri 33 Parepare, totaling 16 students consisting of 9 boys and 7 girls. The approach and type of research used is a qualitative approach and the type of research used is classroom action research. The data collection techniques used are observation, tests and documentation. The focus of the research is the focus on the process and the focus on student learning outcomes on ethnic diversity material by applying learning video media. In cycle I the results of research on the learning process are in good qualification (B) and the results of learning tests are in sufficient qualification (C), while in cycle II the results of research on the learning process are in good qualification (B) and the results of learning tests are in qualification good (B). The conclusion in this study is that the use of learning video media can improve the process and learning outcomes about ethnic diversity in class V UPTD SD Negeri 33 Parepare.